2020
DOI: 10.3390/jcm9103215
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Triceps Surae Muscles in Patients Undergoing Anterior Cruciate Ligament Reconstruction: A Matched Case-Control Study

Abstract: A limited number of studies has investigated the gastrocnemius and soleus in patients undergoing anterior cruciate ligament reconstruction (ACLR). This study investigated the muscle strength (Nm kg−1 × 100) and reaction time (acceleration time (AT), milliseconds) of thigh and calf muscles in patients undergoing ACLR. Thirty-two patients with ACLR and 32 normal control subjects were included. One year postoperatively, the strength of thigh muscles was significantly reduced after ACLR compared with that of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Isometric testing with a hand-held dynamometer was the most common method of strength assessment (16 studies). The remaining 12 studies measured slow speed concentric strength using computerised isokinetic dynamometers (≤120°/s),13 14 40 43–47 51–57 with 2 also measuring eccentric strength 46 54. Hip external and internal rotation strength were only measured with hand-held dynamometers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Isometric testing with a hand-held dynamometer was the most common method of strength assessment (16 studies). The remaining 12 studies measured slow speed concentric strength using computerised isokinetic dynamometers (≤120°/s),13 14 40 43–47 51–57 with 2 also measuring eccentric strength 46 54. Hip external and internal rotation strength were only measured with hand-held dynamometers.…”
Section: Resultsmentioning
confidence: 99%
“…55 59 60 Outcome measurement was reliably reported with detailed methodology and low risk of bias for all except four studies 50 52 53 58. Ten studies suffered from unclear selection bias 40 42–44 46 47 51 56 57 61. Of the intervention trials included, three out of six had high risk of bias in randomisation methods (sequence generation and concealment), and blinding methods, respectively 40 52 53.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LSI value is the ratio of the muscle strength of the opposing limbs and calculated as the mean score for the injured limb divided by the uninjured limb × 100% 36 . A previous study demonstrated that the intergroup differences in quadriceps muscle strength (> 10%) were clinically significant after ACLR 37 . A priori power analysis was calculated using repeated-measures analysis of variance (RM-ANOVA), indicated that a minimum 48 patients (effect size f (V): 0.516, P (η 2 ) = 0.210) would be needed to detect an intergroup difference in quadriceps muscle strength > 10% (α = 0.05, power = 0.8).…”
Section: Methodsmentioning
confidence: 97%